Mitochondrial function in skeletal muscle of patients with protracted critical illness and ICU-acquired weakness. Issue 1 (December 2015) - Jiroutková, Kateřina; Krajčová, Adéla; Ziak, Jakub; Fric, Michal; Waldauf, Petr; Džupa, Valér; Gojda, Jan; Němcova-Fürstová, Vlasta; Kovář, Jan; Elkalaf, Moustafa; Trnka, Jan; Duška, František
Abstract Background Mitochondrial damage occurs in the acute phase of critical illness, followed by activation of mitochondrial biogenesis in survivors. It has been hypothesized that bioenergetics failure of skeletal muscle may contribute to the development of ICU-acquired weakness. The aim of the present study was to determine whether mitochondrial dysfunction persists until protracted phase of critical illness. Methods In this single-centre controlled-cohort ex vivo proof-of-concept pilot study, we obtained vastus lateralis biopsies from ventilated patients with ICU-acquired weakness (n = 8) and from age and sex-matched metabolically healthy controls (n = 8). Mitochondrial functional indices were measured in cytosolic context by high-resolution respirometry in tissue homogenates, activities of respiratory complexes by spectrophotometry and individual functional capacities were correlated with concentrations of electron transport chain key subunits from respiratory complexes II, III, IV and V measured by western blot. Results The ability of aerobic ATP synthesis (OXPHOS) was reduced to 54 % in ICU patients (p <0.01), in correlation with the depletion of complexes III ( 38 % of control, p = 0.02) and IV ( 26 % of controls, p <0.01) and without signs of mitochondrial uncoupling. When mitochondrial functional indices were adjusted to citrate synthase activity, OXPHOS and the activity of complexes I and IV were not different, whilst the activities of complexes II and III were increased in ICU patients 3-fold (p <0.01) respectively 2-fold (p <0.01). Conclusions Compared to healthy controls, in ICU patients we have demonstrated a 50 % reduction of the ability of skeletal muscle to synthetize ATP in mitochondria. We found a depletion of complex III and IV concentrations and relative increases in functional capacities of complex II and glycerol-3-phosphate dehydrogenase/complex III.